Prevalence of Legionella species isolated from shower water in public bath facilities in Toyama Prefecture, Japan. Issue 5 (May 2017) - Kanatani, Jun-ichi; Isobe, Junko; Norimoto, Shiho; Kimata, Keiko; Mitsui, Chieko; Amemura-Maekawa, Junko; Kura, Fumiaki; Sata, Tetsutaro; Watahiki, Masanori
Abstract: Aims: We investigated the prevalence of Legionella spp. isolated from shower water in public bath facilities in Toyama Prefecture, Japan. In addition, we analyzed the genetic diversity among Legionella pneumophila isolates from shower water as well as the genetic relationship between isolates from shower water and from stock strains previously analyzed from sputum specimens. Methods: The isolates were characterized using serogrouping, 16S rRNA gene sequencing, and sequence-based typing. Results: Legionella spp. were isolated from 31/91 (34.1%) samples derived from 17/37 (45.9%) bath facilities. Isolates from shower water and bath water in each public bath facility were serologically or genetically different, indicating that we need to isolate several L. pneumophila colonies from both bath and shower water to identify public bath facilities as sources of legionellosis. The 61 L. pneumophila isolates from shower water were classified into 39 sequence types (STs) (index of discrimination = 0.974), including 19 new STs. Among the 39 STs, 12 STs match clinical isolates in the European Working Group for Legionella Infections database. Notably, ST505 L. pneumophila SG 1, a strain frequently isolated from patients with legionellosis and from bath water in this area, was isolated from shower water. Conclusions: Pathogenic L. pneumophila strains including ST505 strain were widely distributed in shower water in public bath facilities, with genetic diversity showing several different origins. This study highlights the need to isolate several L. pneumophila colonies from both bath water and shower water to identify public bath facilities as infection sources in legionellosis cases.